Identifying the Dimensions of Employer Brand Attractiveness: Students’ Perspective Vs. Employees’ Perspective - Trott, Sangeeta (Prabandhan: Indian Journal of Management, 2013)
Purpose: The purpose of the paper is to find out the most important factor for employer brand attractiveness from the perspective of the students as well the employees. Data Collection: Data was collected from B-school students and middle level employees of Mumbai region. 406 respondents were chosen for the purpose. The data was collected by using an online questionnaire. About 177 responses were received in the students’ category and 77 responses were received in the employee category. Data Analysis: The data was analyzed using SPSS. Descriptive statistics and Factor Analysis were used to analyze the data further. The data analysis revealed some interesting results. Managerial Implications: The study would be of great use to the marketers in designing strategies for good employer brand attractiveness. Limitations: The major limitation of the study was the limited sample size.